Effect of Plukenetia volubilis Linneo (sacha inchi) on postprandial triglycerides - Huamán, Juan (2008)
Introduction: Postprandial lipemia is a coronary risk factor and is affected by omega-3 fatty acids. There is evidence that omega-3 acids decrease plasma lipids. Plukenetia volubilis Linne (sacha inchi) is rich in omega-3. Objectives: To determine the effect of sacha inchi ingestion on postprandial triglycerides in young adults. Design: Quasi-experimental study. Setting: Faculty of Medicine, Universidad Nacional de Trujillo. Participants: Medical students. Interventions: To 12 randomly selected Universidad Nacional de Trujillo medical students we performed oral glucose tolerance test in two phases: in the first following the ingestion of 82 grams of olive oil and in the second adding 50 grams of sacha inchi. Main outcome measures: Plasma lipids reduction. Results: In the first phase we obtained an average of 99,67 mg/dL basal triglycerides that following the ingestion of the olive oil increased in 32 at 1½ h, 74 at 3 h, 89 at 4½ h and 54 at 6 h average; in the second phase, average basal value was 100,92 mg/dL and after the olive oil and sacha inchi it increased in 15 at 1½ h, 52 at 3 h, 41 at 4½ h, and 43 at 6 h, these values were significantly lower at 1½ h (p=0,02) and 4½ h (p=0,0035). Following the consumption of sacha inchi the triglyceride tolerance test graphic showed statistical significance in the area under the curve in both phases (38,17%; p=0,0080). Conclusions: Plukenetia volubilis Linneo consumption decreases postprandial triglycerides in young adults.